Odontogenic Keratocyst Treatment Modalities. A Narrative Review and Case Report - Muñoz-Pereira, Mauricio E.; Ruiz-Imbert , Ana C.; Piedra Trejos, Gloriana (Odovtos - International Journal of Dental Sciences, 2023)
The odontogenic keratocyst (OKC) is a benign lesion that arises from dental lamina remnants or basal cells of the overlying epithelium. In 2005, the World Health Organization categorized OKCs as tumors due to their aggressive behavior. However, in 2017 due to the lack of evidence, it was reclassified as an odontogenic cyst with aggressive behavior. This report describes a clinical case of a 20-year-old male who visited the dental clinic at the University of Costa Rica for third molar removal. As an incidental radiographic finding, an intraosseous lesion in the right side of the mandible was detected. The patient was asymptomatic, with an augmented mass in the right posterior sulcus and crepitation at palpation. Decompression, enucleation followed by peripheral ostectomy, and incisional biopsy were performed, and a personalized and handmade acrylic appliance was fitted into the surgical window until it closed. No recurrence has been documented after 6 years. The continuous debate regarding OKC’s classification by the WHO challenges the odontology community to constantly update its knowledge in the treatment modalities, taking into consideration the availability of resources and recurrence rates. The aim of this paper is to present the treatment and long-term follow-up of an OKC management and concomitantly review its main treatment options.